أثر انموذج ((PhET على تنمية التفكير البصري لدى طالبات الصف الحادي عشر علمي في مادة الفيزياء - صبري, أ.د. وعد محمد نجاة; علي, لانه لطيف (Sulaimani Journal for Humanities, 2023)
The aim of the current research is to find out the effect of using the PhET model on the development of visual thinking among eleventh grade students in physics. The experimental approach was used by designing two equal groups with a pre-test and post - test, which is called the experimental design with partial control. The research sample was chosen for the students by the intentional method. The teaching subjects were conducted in a random manner from the eleventh-grade students, which numbered (56) students, (27) students from the experimental group and (29) students from the control group. The educational units were applied to the experimental group using the(PhET) model and the control group in the usual way. For a period of (12) weeks (one semester) and (4) lessons per week by the researcher, and the results were processed by appropriate statistical methods. The researcher concluded the effect of using the (PhET) model showed a remarkable development in the development of visual thinking among the students of the experimental group, and this was indicated by the significant differences between the pre and post - tests and in favor of the post tests. in the search dependent variable.
Keywords: (PhET(model; thinking; visual thinking